Penggunaan Media Pembelajaran Swimming board dalam Pengembangan Afektif: Penggunaan Media Pembelajaran Swimming board dalam Pengembangan Afektif - Rahmat Permana (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2016)
The problem is the reference authors in this research is to reveal the influence of the media or teaching aids in swimming. The study was conducted in Bandung ganesha School mandala swimming with the sample at the level swimmers who have not received a base class breaststroke swimming lessons. The purpose of this study was to determine the influence of the media in the development of swimming board psychomotor, cognitive and affective. The method used in this study are pre experimental method with a population of 10 people swimmer basis, the determination of the total sample population of the swimmers who have not given breaststroke swimming lessons numbered 10 people. After treatment of the sample given the findings show that the use of swimming board significantly influence the development of breaststroke swimming skills with Sig. 0.000> 0.05.